(untitled) (Perner’s Contacts, 2015)
Criminal cases in logistic centers are currently phenomenon that affects most companies in the industry. Actual data indicate a trend of increasing the number of registered criminal cases in absolute terms. The total volume of inventory differences in the last decade shows a trend of gradual decrease. Management of logistic centers adopt various measures to efficient processes control, especially measures to reduce the impact of criminal activities. The process of effective control of human capital in connection with the creation of criminal phenomena, it is necessary to continuously control. Following this can take specific measures that will be effective for that particular company (logistic center).